2010
DOI: 10.1159/000312381
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Hepcidin in Patients on Maintenance Hemodialysis: Role of Inflammation

Abstract: Background/Aim: Hepcidin could be one of the most important regulators for iron metabolism in patients on maintenance hemodialysis (MHD). The factors affecting serum hepcidin levels were evaluated among indexes of anemia, iron metabolism, or inflammation, as well as the dose of erythropoietin. Methods: 198 MHD patients treated with recombinant human erythropoietin were recruited and serum hepcidin-25 levels were specifically measured by liquid chromatography tandem mass spectrometry. Results: In multivariate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
66
5
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 42 publications
9
66
5
1
Order By: Relevance
“…In contrast, no relationship was observed between hepcidin and hsCRP levels, or between hepcidin levels and EPO (ESA) dose, which is consistent with previous studies. 12 Several factors may explain this lack of relationship, including differences in the half-lives of hsCRP and hepcidin. 22,23 Another explanation may be the distinct features of the study population, 20 Previous studies have shown that comparison between hepcidin and hsCRP may serve as a quick and easy method for identifying the difference between iron deficiency, microinflammation or mixed anaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, no relationship was observed between hepcidin and hsCRP levels, or between hepcidin levels and EPO (ESA) dose, which is consistent with previous studies. 12 Several factors may explain this lack of relationship, including differences in the half-lives of hsCRP and hepcidin. 22,23 Another explanation may be the distinct features of the study population, 20 Previous studies have shown that comparison between hepcidin and hsCRP may serve as a quick and easy method for identifying the difference between iron deficiency, microinflammation or mixed anaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The ESA resistance index (ERI) was calculated as the ratio of the weekly EPO dose to Hb per unit weight. 12 The single-pool urea clearance index was used to represent weekly dialysis dose and was calculated as K t /V, where K is the clearance of urea by the dialyser, t is the dialysis time and V is the volume of distribution of urea. …”
Section: Sample Collection and Laboratory Measurementsmentioning
confidence: 99%
“…It has been suggested that the serum hepcidin levels of CKD patients are higher compared with those of healthy individuals. However, a recent study revealed that the serum hepcidin levels of all HD patients were not necessarily significantly higher compared with those of healthy individuals and that the serum hepcidin levels in 46% of HD patients were within the healthy range [161]. Thus, it is possible that in HD patients with small liver iron stores, the hepcidin level is low and the absorption of iron through the digestive tract may not be inhibited.…”
Section: (2)administration Route Of Iron For Hd Patientsmentioning
confidence: 97%
“…Hepcidin in CKD also has been associated with iron-restricted erythropoiesis, as reflected by the relation of hepcidin with lower hemoglobin and/or reticulocyte counts (31,169,171 ). Furthermore, CRP and IL-6 were shown to be less relevant predictors in the setting of renal insufficiency (16,170,(172)(173)(174)(175). Intravenous iron administration was found not to influence hepcidin concentrations in hemodialysis (HD) patients that were withheld from iron and ESA therapy for 2 weeks (169 ), whereas it increased hepcidin in iron-naïve CKD patients (31,96 ).…”
Section: Disorders Associated With Hepcidin Excessmentioning
confidence: 99%